The role of women’s empowerment in food crises prevention and mitigation under climate stress - Ringler, Claudia; Bryan, Elizabeth; Nanavaty, Reema (Pontifical Academy of Sciences, 2024)
Despite small improvements, gender and social inequalities remain pervasive; they lead to worse outcomes for women and children and Indigenous populations during food, energy, and environmental, including climate, crises, widening gaps in access to food and employment and increasing overall inequity in income between the rich and the poor. At the same time there is considerable evidence that women have large roles to play in crisis mitigation, particularly in the most vulnerable populations, and that their engagement in decision-making processes supports crisis prevention. To avoid that humanitarian and food crises increase gender and social inequities and to ensure that women can exert their agency in reducing crises impacts, governments, donors and practitioners need to actively work with and for women, girls and Indigenous populations, providing opportunities for their active participation in decision-making processes and policy responses at all levels, ensuring access to digital tools, information, finance, and raising awareness on and actively working toward preventing gender-based violence.